2022
DOI: 10.7759/cureus.30862
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sirtuin 1 Levels in Peripheral Blood Mononuclear Cells of Patients With Idiopathic Pulmonary Fibrosis

Abstract: Aim: Idiopathic pulmonary fibrosis (IPF) is a devastating lung disorder that is characterized by aggressive and dysbalanced wound healing. IPF is mainly a disease of the elderly and thus is likely to share common pathophysiologic mechanisms with other more age-related diseases. Emerging evidence has linked disturbance of sirtuin-1 (SIRT1) expression and activity with aging and diseases of the elderly. In the present study, we aimed to evaluate SIRT1 expression in the peripheral blood mononuclear cells (PBMCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A study by Deskata et al in 2022 assessed SIRT-1 levels in plasma and peripheral blood mononuclear cells (PBMC) of IPF patients, and reported significantly lower levels in PBMC from IPF patients compared to controls. Furthermore, the authors concluded that SIRT-1 is predictive of IPF when adjusted for sex and age [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Deskata et al in 2022 assessed SIRT-1 levels in plasma and peripheral blood mononuclear cells (PBMC) of IPF patients, and reported significantly lower levels in PBMC from IPF patients compared to controls. Furthermore, the authors concluded that SIRT-1 is predictive of IPF when adjusted for sex and age [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that SIRT1 levels were statistically significantly lower in the supernatant of PBMCs from patients with IPF compared with those from controls. Furthermore, the likelihood of being in the IPF group was increased by older age and lower SIRT1 levels [ 34 ]. Notably, the activation or overexpression of SIRT1 by resveratrol treatment attenuates the TGF-β1-induced myofibroblast activation by regulating the expression of p300 [ 35 ].…”
Section: Sirtuins In Idiopathic Pulmonary Fibrosis: Focus On Putative...mentioning
confidence: 99%